Improved Synthesis and Preparation of Analogues of a Pain-Relieving Pyridin-2(1H)-one - Frazier, Théo; Murail, Pauline; Giraud, Francis; Artola, Alain; Dallel, Radhouane; Anizon, Fabrice; Moreau, Pascale (Synthesis, 2024)
An optimization of the synthesis of 3,5-disubstituted pyridin-2(1H)-ones with in vivo anti-allodynic activity was conducted. The optimized synthesis was employed to prepare novel analogues which were then assessed for their efficacy in preventing cutaneous mechanical allodynia in a male rat hindpaw capsaicin model.
Keywords: pyridin-2(1H)-ones; synthesis optimization; palladium catalysis; mechanical allodynia; analgesics